Functional annotation of human cytomegalovirus gene products: an update - Van Damme, Ellen; Van Loock, Marnix (Frontiers in Microbiology, 2014)
Human Cytomegalovirus is an opportunistic double-stranded DNA virus with one of the largest viral genomes known. The 235kB genome is divided in a unique long (UL) and a unique short (US) region which are flanked by terminal and internal repeats. The expression of HCMV genes is highly complex and involves the production of protein coding transcripts, polyadenylated long non-coding RNAs, polyadenylated anti-sense transcripts and a variety of non-polyadenylated RNAs such as microRNAs. Although the function of many of these transcripts is unknown, they are suggested play a direct or regulatory role in the delicately orchestrated processes that ensure HCMV replication and life-long persistence. This review focuses on annotating the complete viral genome based on three sources of information. First, previous reviews were used as a template for the functional keywords to ensure continuity; second, the Uniprot database was used to further enrich the functional database; and finally, the literature was manually curated for novel functions of HCMV gene products. Novel discoveries were discussed in light of the viral life cycle. This functional annotation highlights still poorly understood regions of the genome but most importantly it can give insight in functional clusters and/or may be helpful in the analysis of transcriptomics and proteomics studies.